Prioritisation of code clones using a genetic algorithm - Azadi, Umberto; Walter, Bartosz; Fontana, Francesca Arcelli (Information and software technology, 2024)
Code clones are prevalent, and due to their diverse impact on projects’ quality they require a proper management strategy. Develop GA-based Refactoring-Aware Detection (RAD) approach for prioritisation of code clones. A genetic algorithm (GA) that balances estimated gain and cost/risk of refactoring to select the optimal clone candidate to refactor. GA converges on a solution, with diverse variance. The value of fitness function is higher for multi-objective approaches, but they also exhibit higher variance. GA can be effectively applied for clone prioritising.